Aldehyde Carboxylation: A Concise DFT Mechanistic Study and a Hypothetical Role of CO2 in the Origin of Life - Juhl, Martin; Kim, Myungjo J.; Lee, Hee-Yoon; Baik, Mu-Hyun; Lee, Ji-Woong (Synlett, 2019)
Carbon dioxide is arguably one of the most stable carbon-based molecules, yet enzymatic carbon fixation processes enabled the sustainable life cycle on Earth. Chemical reactions involving CO2-functionalization often suffer from low efficiency with highly reactive substrates. We recently reported mild carboxylation of aldehydes to furnish α-keto acids – a building block for chiral α-amino acids via reductive amination. Here, we discuss potential reaction mechanisms of aldehyde carboxylation reactions based on two promoters: NHCs and KCN in the carboxylation reaction. New DFT mechanistic studies suggested a lower reaction barrier for a CO2-functionalization step, implying a potential role of CO2 in prebiotic evolution of organic molecules in the primordial soup.1 Introduction: Aldehydes, Benzoins, Carboxylic Acids2 CO2-Activation: NHC, Cyanide, Lewis Acid and Water3 A Breslow Intermediate: Benzoin Reaction vs. Carboxylation with CO24 Carboxylation in the Primordial Soup5 Conclusion
Keywords: carbon dioxide; umpolung; origin of life; cyanide; amino acids